Revealing the Meanings of Prince Harry’s First Speech after Royal Split: Systemic Functional Grammar Analysis - Widi Handayani (Journal of Language and Literature, 2021)
The speech is delivered by Prince Harry. Three areas of SFG are applied to analyze the speech. The result shows that in terms of ideational metafunction, material, and mental processes are 2 highest occurrences in the speech. It happens since the speaker displays all his concrete actions including doing charity and meeting many people of his country. Through mental process, it shows that he involves his senses to communicate the language in his mind. Three types of mental process, namely cognition, affection, and perception are found in the speech indicating his empathy to the people towards the news of the royal split. The interpersonal metafunction shows that he does take sides on the wife and family. Using modality, he employs that the media power force creates huge speculations among the citizens. They accuse his wife for bringing bad impacts for him. By applying high commitment of modality, he reassures people that his wife is not the cause of the split. He also requests the people to love her as much as they love him. The modality shows that the split will not change the commitment he has for serving the country. The polarity displays a clarification that the decision of splitting is taken after long consideration. The personal pronoun ‘I’ shows that the speaker is the subject matter of the speech. The textual metafunction in the speech shows that unmarked theme deploys the idea that it is a declarative speech which functions to give information or clarification. The additional conjunction is used to explore detailed information people must know.